Borderline‐low testosterone levels are associated with lower left ventricular wall thickness in firefighters: An exploratory analysis. (3rd September 2020) - Lofrano‐Porto, Adriana; Soares, Edgard M. K. V. K.; Matias, Alexs; Porto, Luiz Guilherme Grossi; Smith, Denise L.
Abstract: Background: Low endogenous testosterone has been associated with increased cardiovascular risk in men. Objectives: To determine the prevalence of low serum testosterone level (TT) in a cohort of male US career firefighters and to examine its relation with left ventricular wall thickness (LVWT). Materials and Methods: We conducted a cross‐sectional study among 341 career firefighters, (age: 37.5 ± 10.3 years; BMI: 28.9 ± 4.5 kg/m 2 ), who underwent an occupational medical screening examination. TT quartiles were determined, and LVWT distribution among them was plotted. Then, TT values were categorized as low (<264 ng/dL), borderline (264‐399 ng/dL), reference range (400‐916 ng/dL), and high (>916 ng/dL). To further investigate the association of mildly decreased TT on LVWT, we divided the borderline group into borderline‐low (264‐319 ng/dL) and borderline‐high (320‐399 ng/dL) ranges. LVWT values were classified as low LVWT when <0.6 cm. A multivariate model was used to compare LVWT, age, BMI, systolic blood pressure (SBP), and HbA1c among groups by TT values. Results: The prevalence of low TT was 10.6% and of borderline was 26.4%, while 58.7% had levels in the reference range. The low‐TT group was older and had higher BMI and SBP as compared to the reference group ( P  < .01). LVWT values were different among groups ( P  = .04) and significantly lower in firefighters with borderline‐low TT as compared to the reference group ( P  < .05). This finding also occurred within obese firefighters ( P  = .03). The borderline‐low group had a higher adjusted risk for a low LVWT as compared to the reference group [OR: 4.11 (95% CI: 1.79‐9.43)]. Discussion: Our findings highlight the possible relationship between a mild reduction in testosterone levels (borderline) and lower LVWT. Conclusions: A high prevalence of subnormal TT levels (low and borderline: 37%) was observed in this relatively homogeneous cohort of career firefighters. Mildly decreased TT levels and lower LVWT might represent a preclinical condition and a window of opportunity for cardiovascular preventive interventions in firefighters.